Preliminary geotechnical planning for the installation of a heavy and restructured collective transport system in Sfax, Tunisia - ELLEUCH, Hana; ROUIS, Jamel (Revue Internationale du Chercheur, 2026)
Sfax represents one of the most spread out cities in Tunisia, covering a surface area of 220 km2 that englobes a half million urban dwellers. The service quality of the existing public transport system is perceived to deteriorate, registering reduced travel frequency rates ranging between 15 and 60 minutes. The actual urban transport network prevalent in the city of Sfax is marked with remarkable saturation. As a remedy to this situation, the authorities have reconsidered the need to provide a rather competitive public transport system through introducing the tram, as a new transport means. The conducted pre-feasibility studies have provided us with preliminary knowledge as to the appropriate transport corridor for paving the way for the tram line. Accordingly, and for an effective accommodation of the transmission line, the trace must meet certain imposed technical constraints. To this end, an efficient geometric study need be conducted, whereby, a convenient feasibility map for inserting the first tram into Sfax transport network could be effectively drawn. In this respect, the authorities must consider the creation of a mass transport system that breaks away with the traditional modes, such as air mode. The mission accorded to the pre-project geotechnical study team is aimed to recognize the mechanical characteristics of the soil. Seven zone is identified in the geotechnical results.